Using georaphic information system (GIS) as a supporting tool in public facilities planning - 418975 Imtiaz Ahmed Chandio; Ahmad Nazri Muhamad Ludin, Prof. Dato', supervisor; Wan Yusryzal Wan Ibrahim, supervisor; Fakulti Alam Bina (2009)
Thesis (Sarjana Sains (Perancangan - Teknologi Maklumat )) - Universiti Teknologi Malaysia, 2009